PEMETAAN PERKEMBANGAN EKONOMI ANTAR DAERAH DI INDONESIA - Fahrudin Ramly; Ali Tutupoho (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2020)
Equitable distribution of development results in various regions has become a new paradigm in current national development policies. However, in reality, inequalities in development between regions, both between provinces and regions, are still encountered. This study aims to map the economic development between regions in Indonesia. Referring to the amount of GRDP in each province and region, there is a huge difference. Provinces which are located in Java Island, have a large GRDP contribution to GDP. This means that the Indonesian economy is still concentrated in these areas.